The Effect of Agricultural Policy, Infrastructure, and Market Quality on the Sustainability of Food Crop Farming in West Java - Lubis, Mitra Musika; Sarie, Fatma; Judijanto, Loso; Ramlan, Winarto (West Science Interdisciplinary Studies, 2023)
This research investigates the interplay between agricultural policy, infrastructure, market quality, and the sustainability of food crop agriculture in West Java through a quantitative analysis. A sample of 148 participants provided insights into their perceptions, contributing to a comprehensive understanding of the factors influencing agricultural sustainability. The measurement model demonstrated high reliability and validity, while the structural model revealed significant positive relationships between agricultural policy, infrastructure, market quality, and sustainability. Model fit indices confirmed the adequacy of the proposed framework. The findings have implications for policymakers and practitioners, guiding strategies to enhance agricultural sustainability. While the study enriches the existing literature, limitations and avenues for future research are acknowledged.